Variability and creativity in small-sided conditioned games among elite soccer players. (May 2020) - Caso, Simone; van der Kamp, John
Abstract: Objective: Small-sided conditioned games (SSCG) in soccer are games with a small number of players, often played on smaller than regular pitches and with adapted rules. It has been argued that SSCG foster soccer players' physical, technical and tactical performances and creativity. This study tested the latter conjecture by analysing video-footage of individual actions of elite soccer players in 5 v 5, 6 v 6, 7 v 7 SSCG played during regular training sessions and 11-aside training matches. Based on the ecological dynamics approach, we hypothesized that smaller formats would result in players making more individual actions. We additionally anticipated that the smaller formats players would induce a larger repertoire of actions, that is, an increased variability of actions, and that such increase in variability would be associated with more creative actions. Along the same lines, we reasoned that midfielders would make more creative actions than defenders and attackers. Method: We categorized 3555 soccer actions on the ball and without the ball of 24 elite soccer players. Results: Players produced more actions in smaller SSCG formats compared to the larger SSCG format and the 11-aside match. They also produced more different actions in SSCG than the 11-aside match. Furthermore, ten creative actions (i.e., actions that were adequate and only made by one or two players) were discerned. The creative actions emerged most often in the smaller SSCG, and were absent in the 11-aside matches. Finally, strikers, defenders and midfielders did not show reliable differences in terms of number, variability and creativity of action. Conclusion: SSCG in soccer do indeed stimulate variability and creativity of individual actions. It is important to confirm whether these immediate effects of SSCG generalize across longer time scales. Highlights: Elite soccer players actions in small-sided conditioned games (SSCG) were analysed. Elite soccer players produced more actions in smaller SSCG. Elite soccer players showed a larger action repertoire in smaller SSCG. Elite soccer players made more creative action in smaller SSCG. Smaller SSCG can be used to increase the occurrence of creative actions.